2009
DOI: 10.1136/ard.2009.117622
|View full text |Cite
|
Sign up to set email alerts
|

Tumour necrosis factor α −308G→A polymorphism is not associated with response to TNFα blockers in Caucasian patients with rheumatoid arthritis: systematic review and meta-analysis

Abstract: According to this meta-analysis, the TNFA -308 polymorphism is not a predictor of the clinical response to anti-TNF treatment in RA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(47 citation statements)
references
References 35 publications
2
42
0
1
Order By: Relevance
“…Some studies have reported a positive association of TNF-α -308 alleles with RA 3,16,31-34 while others have reported lack of association with RA. 36,[48][49][50][51][52] In conformity with the majority of previous studies, the present study failed to demonstrate any association between the TNF-α -308 G>A promoter polymorphism and RA in cohort 1. Interestingly, the comparison between RA patients who were RF positive and RF negative revealed a marginally significant difference in the allele frequencies (p=0.05, OR=2.86, 0.96-8.52 at 95% CI).…”
Section: Discussionmentioning
confidence: 31%
“…Some studies have reported a positive association of TNF-α -308 alleles with RA 3,16,31-34 while others have reported lack of association with RA. 36,[48][49][50][51][52] In conformity with the majority of previous studies, the present study failed to demonstrate any association between the TNF-α -308 G>A promoter polymorphism and RA in cohort 1. Interestingly, the comparison between RA patients who were RF positive and RF negative revealed a marginally significant difference in the allele frequencies (p=0.05, OR=2.86, 0.96-8.52 at 95% CI).…”
Section: Discussionmentioning
confidence: 31%
“…In complex biologic systems, the effect of a single gene polymorphism in determining cytokine secretion may be affected by factors such as genetic and epigenetic determinants or may be minimized through interaction with environmental factors (Powell et al, 2001;Malleo et al, 2007). Most of all, both SNPs of the TNF-α gene may not be specific to oral cancer although they are associated with many inflammatory diseases (Lu et al, 2008;Pavy et al, 2010;Lee et al, 2012;).…”
Section: Discussionmentioning
confidence: 99%
“…There has been considerable data accumulated here, in particular with regard to single nucleotide polymorphisms (SNPs) which effect the TNF promoter such as -308G>A, and -857C>T. Reports on TNF-308G/A have indicated that a genetic predisposition toward increased TNF expression (carrying the A allele) can be associated with nonresponse to anti-TNF therapy [29][30][31][32]. These findings however have been disputed in a recent meta-analysis by Pavy et al and so the role of this SNP remains unclear [33]. In addition to studies of TNF, SNPs within other cytokine genes such as IL-10, TGF-B1, IL-1B and the IL-1 receptor antagonist IL-RA have also been examined where opposing associations as biomarkers for response and non-response are reported [34,35].…”
Section: Theranostic Biomarkers and Response To Anti-tnf Therapymentioning
confidence: 87%